Osteochondral Allograft Transplantation: Identifying the Biomechanical Impact of Using Shorter Grafts and Pulsatile Lavage on Graft Stability - Babu, Jacob M.; Hodax, Jonathan D.; Fadale, Paul D.; Owens, Brett D. (The Journal of Knee Surgery, 2020)
This study seeks to identify the ability of shorter osteochondral allografts (OCAs) to resist displacement/failure. Additionally, this study seeks to evaluate the effect of pulsatile lavage (PL) on the biomechanical stability of the OCA. Fifteen-millimeter diameter, human cadaveric, OCAs of 4, 7, and 10 mm in depth were harvested for comparison of resistance to compressive and tensile loads. For each group, seven specimens were subjected to tensile loads and three specimens subjected to compressive loads until failure (pullout or subsidence). An additional study group of 10 pulsatile-lavaged OCAs of 15 mm in diameter and 7 mm in depth were introduced for comparison to the original 7 mm depth OCA group. The average tensile forces for failure for the 4, 7, and 10 mm plugs were 23.74, 199.57, and 197.69 N, respectively (p = 1.5 × 10−5). After post hoc analysis of the tensile groups, significant differences in the mean tensile force to failure were appreciated between the 4 and 7 mm groups (p = 4.12 × 10−5) and the 4 and 10 mm groups (p = 1.78 × 10−5) but not between the 7 and 10 mm groups (p = 0.9601). There were no significant differences between the average tensile forces resulting in failure for the 7 mm and 7 mm PL groups (199.57 and 205.2 N, p = 0.90) or compressive forces to failure, respectively (733.6 and 656 N, p = 0.7062). For OCAs of 15 mm in diameter, a commonly used size in practice, plugs of 7 mm in depth showed comparable resistance to pull out and subsidence as 10 mm plugs and significantly better resistance to pull out than 4 mm grafts. PL of allografts prior to insertion did not take away from the structural integrity and stability of the plug.
Keywords: osteochondral allograft; transplantation; osteochondral defect; biomechanical; evaluation; stability; minimum; depth; pulsatile lavage